The ISSUES, CHALLENGES AND MANAGEMENT OF URBAN HOUSEHOLD WATER SUPPLY: AN OVERVIEW IN CASE OF DURAME CITY, KAMBATA TEMBARO ZONE, SNNP REGION, ETHIOPIA JANUARY, 2019 - KIFLE, ZEWDIE; ANISHISO, ALEMU; THOMAS, TEMESGEN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The provision of urban infrastructure like water service has become a major concern in many developed and developing countries. Access to safe water and sanitary means of waste disposal is universal needs and indeed basic human rights. Besides, they are essential elements of human development and poverty alleviation and constitute an obligatory component of primary health care. The main objective of this study is to assess issues, challenges and management of urban household water supply: in case of Durame city, Kambata Tembaro Zone, SNNP Region. The study is descriptive in its nature and both qualitative and quantitative research Approach with a sample size of 120 which selected through systematic random sampling method used. Interview questionnaires were employed for data collection. Lastly the data were analyzed using descriptive statistical tools like frequency and percentage. The study findings revealed that factors like, shortage of water at the sources; rapid population growth, electric power failure, and rapid urbanization were classified to be main causes of water supply shortage to the city communities. The gap between demand and output is increasing from year to year as a result of the aforementioned primary factors. Water source for the city entirely relying only on groundwater is not enough. The study therefore recommends that the groundwater source has to be enlarged by surface water through water conservation techniques. Therefore, as a long- run solution to water supply shortage in the city great attention should be given for surface water development. Furthermore, surface water might serve as a recharging source for groundwater sources in the surrounding area. Through water conservation techniques around the water potential areas (boreholes sites) groundwater have to be recharged so as to balance the recharging and discharging rates. On the other hand, bottom-up community engagement should be promoted, and existing women's groups such as religious, trade, and professional associations should be involved in order to debate how to utilize water responsibly.